Mineralizer effects on the synthesis of amorphous chromium hydroxide and chromium oxide green pigment using hydrothermal reduction method. (February 2015) - Wei, Guangye; Qu, Jingkui; Yu, Zhihui; Li, Yongli; Guo, Qiang; Qi, Tao
Abstract: A chromium oxide green pigment was prepared by thermal decomposition of chromium hydroxide via hydrothermal reduction of a high concentration mixture of Na2 CrO4 (300 g/L) using NaHCO3 as a mineralizer. The mineralizer effects on the hydrothermal process, conversion of chromate, properties of amorphous Cr(OH)3, and color performance of Cr2 O3 were investigated. Compared with sodium carbonate and urea, sodium bicarbonate significantly reduces the Na2 CrO4 concentration and, consequently, improves the conversion of Na2 CrO4 during the hydrothermal process. Additionally, homogeneous particles were obtained by adding NaHCO3 . The changes in the amount of trapped water, oxygen chemisorption, and negative charge on the surfaces of chromium hydroxide particles caused by adding a mineralizer were analyzed using Fourier-transform infrared spectroscopy and zeta potential analysis. The Cr2 O3 pigments were characterized using X-ray diffraction, scanning electron microscopy, and an automatic differential colorimeter. A good color performance by the Cr2 O3 pigment, comparable to that of a commercial pigment, was obtained. Graphical abstract: An appropriate amount of mineralizer was contributed to reach high conversion of chromate and form homogeneous amorphous chromium hydroxide particles, promoting good color performance of a Cr2 O3 green pigment, comparable to that of a commercial pigment. Highlights: Good color performance of Cr2 O3 pigment was prepared by hydrothermal reduction. The conversion of chromate easily reaches 99 wt% by adding NaHCO3 . Mineralizer promotes the agglomeration of chromium hydroxide. Mineralizer changes surface properties of chromium hydroxide. Mineralizer affects the formation of Cr(III) complex and chromium hydroxide.